Components + aspects: a general overview - Reina Quintero, Antonia M.; Torres, Jesús (Revista Colombiana de Computación, 2004)
In the last few years, new ways of decomposing systems have been proposed. First, component-oriented development has been widely recognized as a paradigm for developing systems using pieces called components. But more recently, a new philosophy known as advanced separation of concerns or aspect-oriented programming has arisen. This paradigm has as one of its main aims the improvement of systems’ decomposition. Although at first sight it seems that both approaches clash, they are not incompatible. Therefore, the main goal of this paper is to analise the different proposals to bridge the gap between components and aspects. Keywords: Aspect oriented programming, advanced separation of concerns, component technology.